2012
DOI: 10.1007/s10875-012-9788-7
|View full text |Cite
|
Sign up to set email alerts
|

CCR7+ Central and CCR7− Effector Memory CD4+ T Cells in Human Cutaneous Leishmaniasis

Abstract: A combination of Leishmania-reactive IFN-γ producing CD4(+)CD45RO(+)CD45RA(-)CCR7(-) T(EM) and Leishmania-reactive IL-2 producing CD4(+)CD45RO(+)CD45RA(-)CCR7(+) T(CM) are identified in individuals with history of CL which might play a role in protective recall immune response against Leishmania infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…Giving support to our data, previous observation in mouse model of L. major infection indicates that effector memory CD4+ T cells are the main source of IFN-gamma [8]. Also, it was shown that in subjects with history of CL caused by L. major or L. tropica , effector memory CD4+ T cells were the main source of IFN-gamma production [26]. …”
Section: Discussionsupporting
confidence: 88%
“…Giving support to our data, previous observation in mouse model of L. major infection indicates that effector memory CD4+ T cells are the main source of IFN-gamma [8]. Also, it was shown that in subjects with history of CL caused by L. major or L. tropica , effector memory CD4+ T cells were the main source of IFN-gamma production [26]. …”
Section: Discussionsupporting
confidence: 88%
“…This is important as it allows comparison of the cytokines alterations in a given patient from active‐phase to healed lesions. However, in most of the published data on human leishmaniasis, immune responses of subjects with active and with history of CL have been measured separately, and due to the broad variations of immune responses in every individual, the interpretation of these data may not be always concomitant with precision . The results of the present study showed that TNF‐α levels are significantly reduced in all patients with CL after standard treatment with antimony and clinical cure of lesions, although the intensity of the reductions was different among CL volunteers.…”
Section: Discussionmentioning
confidence: 56%
“…In human leishmaniasis, the mechanisms of protection have not been fully understood, although the phenotypes and effector functions of CD8 + T cells and CD4 + Th1/Th2 lymphocytes have been extensively studied , and the presence of Th17 cells in the skin lesion samples of patients with active CL and role of Th17 cytokines in support of Th1 response in patients with VL have been demonstrated . The role of a number of immune system productions, such as pro‐inflammatory cytokine TNF‐α, IL‐17 and IL‐22 in CL outcome, needs more clarification.…”
Section: Introductionmentioning
confidence: 99%
“…CCR7 + CD4 memory cells that show increased proliferative capacity in response to leishmania antigen have been identified in cutaneous leishmaniasis patients that have healed [66], suggesting that T CM cells are generated by infection in humans and may be a good target in a vaccine.…”
Section: Implications For the Development Of A Cutaneous Leishmanimentioning
confidence: 99%